Evaluation of the cell culture based and the mouse brain derived inactivated vaccines against Crimean-Congo hemorrhagic fever virus in transiently immune-suppressed (IS) mouse model. - Shaikh Terkis Islam Pavel; Hazel Yetiskin; Ahmet Kalkan; Aykut Ozdarendeli (PLoS Neglected Tropical Diseases, 2020)
Crimean-Congo hemorrhagic fever virus (CCHFV) is a tick-borne virus in the Nairoviridae family within the Bunyavirales order of viruses. Crimean-Congo hemorrhagic fever (CCHF) is the most widespread among tick-borne human viral diseases. It is endemic in many areas of Africa, Asia, the Middle East, in the Balkans, Russia and countries of the former Soviet Union. The confirmed CCHF cases were seen in Spain in 2016 to signify expansion of the virus into new geographical areas. CCHFV causes a viral human disease characterized by sudden onset of fever, headache, abdominal pain, nausea, hypotension, hemorrhage, and hepatic dysfunction with fatality rates up to 30%. Currently, there are no spesific treatments or licensed vaccines available for CCHFV. The absence of a susceptible animal model for CCHFV infection was severely hindered work on the development of vaccines. However, several animal models of CCHFV infection have been recently developed and used to assess vaccine efficacy. In this study, we have used the transiently immune-suppressed (IS) mouse model that MAb-5A3 was used to block IFN-I signaling in immune intact, wild-type mice at the time of CCHFV infection to evaluate the immune response and efficacy of the cell culture based and the mouse brain derived inactivated vaccines against CCHFV. Both vaccine preparations have provided complete protection but the cell culture based vaccine more effectively induced to CCFHV spesific antibodies and T cell responses. This is the first comparison of the cell culture based and the mouse brain derived vaccines for assessing the protective efficacy and the immunogenicity in the IS mouse CCHFV model.